2019
DOI: 10.3389/fnmol.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma—A Neural Crest Derived Embryonal Malignancy

Abstract: Neuroblastoma is a neural crest derived malignancy of the peripheral nervous system and is the most common and deadliest tumor of infancy. It is characterized by clinical heterogeneity with a disease spectrum ranging from spontaneous regression without any medical intervention to treatment resistant tumors with metastatic spread and poor patient survival. The events that lead to the development of neuroblastoma from the neural crest have not been fully elucidated. Here we discuss factors and processes within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
175
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(179 citation statements)
references
References 128 publications
(189 reference statements)
1
175
0
3
Order By: Relevance
“…As proof-of-concept, we generated a modular "all-in-one" vector system based on clinically applied third generation lentiviral self-inactivating (SIN) vectors designed to constitutively express a CAR in combination with NFAT-inducible cytokine expression, for example, IL12 or IL18. Therefore, we further codon-optimized a well-established second generation CAR that targets the cell-surface disialoganglioside G D2 [25], which has restricted expression in normal tissues, but is expressed on several solid tumors, including glioblastoma [26], neuroblastoma [27], and sarcomas [28]. Clinical trials already support the safety and efficacy of G D2 -redirected CAR T cells without undesirable adverse effects [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…As proof-of-concept, we generated a modular "all-in-one" vector system based on clinically applied third generation lentiviral self-inactivating (SIN) vectors designed to constitutively express a CAR in combination with NFAT-inducible cytokine expression, for example, IL12 or IL18. Therefore, we further codon-optimized a well-established second generation CAR that targets the cell-surface disialoganglioside G D2 [25], which has restricted expression in normal tissues, but is expressed on several solid tumors, including glioblastoma [26], neuroblastoma [27], and sarcomas [28]. Clinical trials already support the safety and efficacy of G D2 -redirected CAR T cells without undesirable adverse effects [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of LIN7A in neurons has previously been shown to result in abnormal neuronal migration (36), a feature of neuroblastoma (37). Clinical cases have also shown that loss of the LIN7A loci results in cellular hyperplasia (36).…”
Section: Discussionmentioning
confidence: 96%
“…The depletion of LIN7A in neurons has previously been shown to result in abnormal neuronal migration (36), a feature of neuroblastoma (37). Clinical cases have also shown that loss of the LIN7A loci results in cellular hyperplasia (36).…”
Section: Discussionmentioning
confidence: 99%